Creativity and service innovation: an examination of differences between theory and practice - Gordon, Shaun MacGregor (2016)
This study addresses creativity and innovation literatures and explores the necessity for creativity in the implementation of service innovations in the English National Health Service. In doing so, it examines whether the standard definition of creativity (Stein 1953; Runco and Jaeger, 2012) is sufficient to explain the workplace creative practices associated with the implementation of a service innovation through the replication of best practice.